Diagnóstico de la producción agrícola del barrio Chan, Parroquia Eloy Alfaro, Cantón Latacunga, año 2023 - Baño Caillagua, Jonathan Geovanny (2024)
The diagnosis being an orderly and structured process facilitated the collection of information on the economic, social and productive aspect of the Chan neighborhood, considering their needs, interests and real situation on agricultural production, therefore, the main objective of the research was the diagnosis of agricultural production in the Chan neighborhood, Eloy Alfaro parish, Latacunga canton, year 2023, for the effect three research tasks were developed: To determine which are the main crops in the Chan neighborhood, to know their production indexes, to identify the main causes that limit the agro-economic development of agricultural production in the Chan neighborhood and to present a proposal that strengthens the agro-economy in the Chan neighborhood to contribute to the economic development of the inhabitants of the area. The methodology used was an experimental design of descriptive, deductive, quantitative and qualitative type, with a basic modality that involved the survey, study population and descriptive statistics, for the handling of the interview an analysis and interpretation was developed, which allowed to obtain as a result that the farmers are mainly producers of chocho, and its limitation is the irrigation water, for which we proceeded to focus a proposal based on drip irrigation and training for the planting of Chocho.